AB1002 Aesthetic dissatisfaction in hand osteoarthritis patients, its impact and risk factors. (23rd January 2014) - Liu, R.; Huizinga, T.W.; Kloppenburg, M.
Abstract : Background: Hand osteoarthritis (HOA) leads to aesthetic damage, but its prevalence, impact and risk factors are largely unknown. Objectives: To investigate in HOA patients the prevalence of dissatisfaction with the appearance of their hands, the impact and its risk factors. Methods: Cross-sectional data were used of the ongoing HOSTAS (Hand OSTeoArthritis in Secondary care) study, in which consecutive patients are included, that are diagnosed by the treating rheumatologist with primary HOA. Participants underwent physical examination to assess number of joints with bony joint enlargements (0-30), deformities (0-22) and limitation in mobility (0-22). The Michigan Hand Outcomes (MHQ) questionnaire involves a pain scale and an aesthetic scale, which measures satisfaction (range 1-5) with the appearance of the hands and its impact, namely discomfort in public, depression and/or the interference with normal social activities (range 3-12). A score of <3 was considered as dissatisfaction and a score of <9 as experiencing impact. Scores for right and left hand were averaged. Disability was assessed by the functional index for HOA (FIHOA). Anxiety (0-21), depression (0-21) and illness perceptions were assessed with the Hospital Anxiety and Depression scales (HADS) and Illness Perception Questionnaire (IPQ), respectively. Odds Ratio (OR) with 95% confidence intervals (CI) were calculated using multivariate logistic regression as measures of relative risk for reporting dissatisfaction with appearance or impact due to dissatisfaction of the appearance, adjusted for age, sex and BMI. Results: Of 106 patients (79% women, mean age 60.0 yrs, mean symptom duration 7, 8(SD 8, 0) yrs) 92% met ACR criteria for HOA. 34% were aesthetically dissatisfied and only 7% reported impact due to dissatisfaction. Pain was not associated with dissatisfaction, but was associated with impact (OR 1.13; 95%CI 1.03-1.23). Disability and number of joints with limitation in mobility were positively associated with both dissatisfaction (OR 1.08; 95%CI 1.00-1.16 and OR 1.16; 95%CI 1.06-1.27 respectively) and with impact (OR 1.43; 95%CI 1.13-1.80 and OR 1.18; 95%CI 1.00-1.40 respectively). Bony joint enlargements (OR 1.13; 95%CI 1.03-1.24) and deformities (OR 1.35; 95%CI 1.13-1.61) were positively associated with dissatisfaction, but not with its impact. Depression (OR 1.22; 95%CI 1.02-1.45), anxiety levels (OR 1.26; 95% CI 1.03-1.54) and illness perceptions (more severe consequences, less understanding of OA, experiencing more negative feelings due to OA, and attributing more psychological factors to their disease) were associated with impact due to dissatisfaction with the appearance of the hands. Conclusions: HOA patients who consult secondary care report regularly aesthetic dissatisfaction with their hands. However, this dissatisfaction has a negative impact only in a small group of patients, who also experiences more pain, disability, depression and anxiety and negative illness perceptions. Disclosure of Interest: None Declared.